PARESIA HIPOCALÊMICA PÓS-EPISÓDIO DIARREICO E DIAGNÓSTICOS DIFERENCIAIS: RELATO DE CASO PARESIS HYPOKALEMIC (POST EPISODE OF DIARRHEA) AND DIFFERENTIAL DIAGNOSIS: CASE REPORT - Vanessa Cristina de Sousa Machado; Alex Goulart de Souza; Aline Dumont Braga; Ana Paula Moreira Reis; Glenda Caroline Oliveira Ferreira; Humberto Graner Moreira; Thaís Maia Fernandes; Victor Clarindo Nominato Ribeiro (UniEVANGÉLICA, 2017)
Objective: To describe a case presenting with loss of mobility due to severe diarrheal episodes with dehydration and hypokalemia, as well as to list the differential diagnoses to be investigated in those cases. Case description: Patient with acute gastroenteritis presenting with severe dehydration and hypokalemia, evolving with lower limbs loss of strength. Through a review of the literature, we discuss the main differential diagnoses related to the case, highlighting them according to their clinical importance during the investigation and appropriate therapeutic approach. Final considerations: We emphasize with this case report that an episode of acute gastroenteritis may be associated with several other clinical presentation, such as lower limbs paresis. Therefore, an adequate clinical and propaedeutic evaluation is important, as well as always distinguishing differential diagnoses as possible triggers for atypical symptoms, such as loss of strength in the lower limbs